Filipinos' representations for the self - Sta, Maria, Madelene (Philippine Journal of Psychology, 1999)
Specific meaning-systems were identified that are associated with the Self of Selfhood. These make apparent the norms, beliefs, values and dimensions of behavior which may be significant in a given group to enable one within the group to understand and communicate one's understanding of oneself to others, and to enable one to make sense of one's actions, Analyses on descriptions of of informants about themselves and others show that to be understood and to understand the other, and to obtain identity within the group, the value of exhibiting one's responsibility to one's relationship with the other becomes important. The concept of loob is found to be that which integrates experiences and which functions in the individual's decisions about how he/she should behave. It is within this frame of reference that one embeds pagmamalasakit, pagsusumikap, paghahayag ng kalooban, pagtatago ng kalooban, pagkamasayahin, pagkamatapat - actions associated with Representations for the Self as it is understood and whose meaning is lived in interactions with others.